Precise radial velocities of giant stars: XVI. Planet occurrence rates from the combined analysis of the Lick, EXPRESS, and PPPS giant star surveys - Wolthoff, Vera; Reffert, Sabine; Quirrenbach, Andreas; Jones, Matías I.; Wittenmyer, Robert A.; Jenkins, James S. (Astronomy and astrophysics, 2022)
Context. Radial velocity surveys of evolved stars allow us to probe a higher stellar mass range, on average, compared to main-sequence samples. Hence, differences between the planet populations around the two target classes can be caused by either the differing stellar mass or stellar evolution. To properly disentangle the effects of both variables, it is important to characterize the planet population around giant stars as accurately as possible.Aims. Our goal is to investigate the giant planet occurrence rate around evolved stars and determine its dependence on stellar mass, metallicity, and orbital period. Methods. We combine data from three different radial velocity surveys targeting giant stars: the Lick giant star survey, the radial velocity program EXoPlanets aRound Evolved StarS (EXPRESS), and the Pan-Pacific Planet Search (PPPS), yielding a sample of 482 stars and 37 planets. We homogeneously rederived the stellar parameters of all targets and accounted for varying observational coverage, precision and stellar noise properties by computing a detection probability map for each star via injection and retrieval of synthetic planetary signals. We then computed giant planet occurrence rates as a function of period, stellar mass, and metallicity, corrected for incompleteness. Results. Our findings agree with previous studies that found a positive planet-metallicity correlation for evolved stars and identified a peak in the giant planet occurrence rate as a function of stellar mass, but our results place it at a slightly smaller mass of (1.68 ± 0.59) M⊙. The period dependence of the giant planet occurrence rate seems to follow a broken power-law or log-normal distribution peaking at (718 ± 226) days or (797 ± 455) days, respectively, which roughly corresponds to 1.6 AU for a 1 M⊙ star and 2.0 AU for a 2 M⊙ star. This peak could be a remnant from halted migration around intermediate-mass stars, caused by stellar evolution, or an artifact from contamination by false positives. The completeness-corrected global occurrence rate of giant planetary systems around evolved stars is for the entire sample, while the evolutionary subsets of RGB and HB stars exhibit and , respectively. However, both subsets have different stellar mass distributions and we demonstrate that the stellar mass dependence of the occurrence rate suffices to explain the apparent change of occurrence with the evolutionary stage.